Phylogenentic and enzymatic characterization of psychrophilic and psychrotolerant marine bacteria belong to γ-Proteobacteria group isolated from the sub-Antarctic Beagle Channel, Argentina - Cristobal, Hector Antonio; Benito, Juliana; Lovrich, Gustavo Alejandro; Abate, Carlos Mauricio (Folia Microbiologica)
The phylogenetic and physiological characteristics of cultivable-dependent approaches were determined to establish the diversity of marine bacteria associated with the intestines of benthonic organisms and seawater samples from the Argentine´s Beagle Channel. A total of 737 isolates were classified as psychrophlic and psychrotolerant culturable marine bacteria. These cold-adapted microorganisms are capable of producing cold-active glycosyl hydrolases, such as β-glucosidases, celulases, β-galactosidases, xylanases, chitinases and proteases. These enzymes could have potential biotechnological applications for use in low-temperature manufacturing processesAccording to polymerase chain reaction-restriction fragment length polymorphism analysis of part of genes encoding 16S ribosomal DNA (ARDRA) and DNA gyrase subunit B (gyrB-RFLP), 11 operational taxonomic units (OTU) were identified and clustered in known genera using InfoStat software. The 50 isolates selected were sequencing based on near full sequence analysis of 16S rDNA and gyrB sequences and identified by their nearest neighbors ranging between 96 and 99 % of identities. Phylogenetic analyses using both genes allowed relationships between members of the cultured marine bacteria belonging to the γ-Proteobacteria group (Aeromonas, Halteromonas, Pseudomonas, Pseudoalteromonas, Shewanella, Serratia, Colwellia, Glacielocola and Psychrobacter) to be evaluated. Our research reveals a high diversity of hydrolytic bacteria and their products actuality has an industrial use in several bioprocesses at low-temperature manufacturing. Fil: Cristobal, Hector Antonio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Tucumán. Planta Piloto de Procesos Industriales Microbiológicos (i); Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Salta. Instituto de Investigación para la Industria Química (i); Argentina Fil: Benito, Juliana. Consejo Nacional de Investigaciones Científicas y ...